Conan Doyle and the rhetoric of genre. (28th January 2023) - Kerr, Douglas
Abstract: Arthur Conan Doyle is recognized as a master of narrative. This essay argues that this mastery expresses itself in his management of genre, at a time when social and cultural changes had created a literary environment that saw the emergence of what is now called genre fiction. Crucial elements in the field of literary publishing which his stories served included the expansion of the monthly magazine market, the emergence of the short story as a popular form of fiction, and the appearance of a broad-based new reading public, well educated in the conventions of genre fiction and equipped with reading skills deriving from this 'genre literacy', which an author like Conan Doyle could foster and manipulate for rhetorical effect. I describe the conditions that created a taste for the popular genre fiction on which, somewhat to his chagrin, Conan Doyle's reputation rested. He moved between genres with a versatility rivalled in his time only by Rudyard Kipling. But he also combined genres together in a single work, so as to satisfy or unsettle, disappoint, reward, or wrong-foot his readers pleasurably by playing on the expectations aroused by cues in the tales. Rather than the detective fiction which he made his own, I turn to his experiments in the genre of 'imperial Gothic' to illustrate this, and examine the rhetoric of three short stories with narrative tropes that depend for their effect on the genre literacy of the reading public to whom they were offered.